Development of a physiomimetic model of acute respiratory distress syndrome by using ECM hydrogels and organ-on-a-chip devices - Marhuenda, Esther; Villarino, Alvaro; Narciso, Maria; Elowsson, Linda; Almendros, Isaac; Westergren-Thorsson, Gunilla; Farré, Ramon; Gavara, Núria; Otero, Jorge (Frontiers in Pharmacology, 2022)
Acute Respiratory Distress Syndrome is one of the more common fatal complications in COVID-19, being characterized by a highly aberrant inflammatory response. Pre-clinical models to study the effect of cell therapy and anti-inflammatory treatments have not been able to give a comprehensive understanding of the disease due to its high complexity. In this work, we present a novel physiomimetic in vitro model for Acute Respiratory Distress Syndrome based on the use of lung extracellular matrix-derived hydrogels and organ-on-a-chip devices. Primary alveolar epithelial cells were cultured on top hydrogels fabricated of previously decellularized lung tissue, containing primary lung mesenchymal stromal cells until forming monolayers. Then, cyclic stretch was applied to mimic breathing, and inflammatory response was induced by using a bacteriotoxin hit. Having mimicked the inflamed breathing lung environment, we assessed the effect of an anti-inflammatory drug (i.e dexamethasone) by the study of secretion of the most relevant inflammatory cytokines. To better identify key players in our model, the impact of the individual factors (cyclic stretch, decellularized lung hydrogel scaffold and the presence of mesenchymal stromal cells) was studied separately. Results showed that the developed advanced physiomimetic model presented a more reduced inflammatory response than traditional models, which is in line with what is expected from the response commonly observed in patients. Further, from the different stimuli, it was observed that the use of extracellular matrix hydrogels obtained from decellularized lungs had the greatest impact on the change of the inflammatory response. The developed model opens then the door for further in vitro studies with a better-adjusted response to the inflammatory hit and more robust results in the test of different drugs or the use of cell therapy.